Patient‐reported outcomes from EMILIA, a randomized phase 3 study of trastuzumab emtansine (T‐DM1) versus capecitabine and lapatinib in human epidermal growth factor receptor 2–positive locally advanced or metastatic breast cancer. Issue 5 (12th November 2013) - Welslau, Manfred; Diéras, Veronique; Sohn, Joo‐Hyuk; Hurvitz, Sara A.; Lalla, Deepa; Fang, Liang; Althaus, Betsy; Guardino, Ellie; Miles, David
<x xml:space="preserve">Abstract</x> BACKGROUND This report describes the results of an analysis of patient‐reported outcomes from EMILIA (TDM4370g/BO21977), a randomized phase 3 study of the antibody–drug conjugate trastuzumab emtansine (T‐DM1) versus capecitabine and lapatinib in human epidermal growth factor receptor 2 (HER2)–positive locally advanced or metastatic breast cancer. METHODS A secondary endpoint of the EMILIA study was time to symptom worsening (time from randomization to the first documentation of a ≥ 5‐point decrease from baseline) as measured by the Trial Outcome Index Physical/Functional/Breast (TOI‐PFB) subset of the Functional Assessment of Cancer Therapy–Breast questionnaire. Predefined exploratory patient‐reported outcome endpoints included proportion of patients with a clinically significant improvement in symptoms (per TOI‐PFB) and proportion of patients with diarrhea symptoms (per Diarrhea Assessment Scale). RESULTS In the T‐DM1 arm, 450 of 495 patients had a baseline and ≥ 1 postbaseline TOI‐PFB score versus 445 of 496 patients in the capecitabine‐plus‐lapatinib arm. Time to symptom worsening was delayed in the T‐DM1 arm versus the capecitabine‐plus‐lapatinib arm (7.1 months versus 4.6 months, respectively; hazard ratio = 0.796; P = .0121). In the T‐DM1 arm, 55.3% of patients developed clinically significant improvement in symptoms from baseline versus 49.4% in the capecitabine‐plus‐lapatinib arm (P = .0842). Although similar at baseline, the number of patients reporting diarrhea symptoms increased 1.5‐ to 2‐fold during treatment with capecitabine and lapatinib but remained near baseline levels in the T‐DM1 arm. CONCLUSIONS Together with the EMILIA primary data, these results support the concept that T‐DM1 has greater efficacy and tolerability than capecitabine plus lapatinib, which may translate into improvements in health‐related quality of life. Cancer 2014;120:642–651. © 2013 American Cancer Society.